Distributed Hierarchical IDS For MANET Over AODV+. - Pahlevanzadeh, Bahareh; Samsudin, Azman (2007)
In this paper, we introduce background knowledge of wireless ad hoc networking mobile ad hoc network (MANET) as well as intrusion detection system (IDS) and mobile agents. This research study surveys, studies and compares the existing intrusion detection based on mobile agent for mobile ad hoc networks. Based on our best knowledge from previous researches we design distributed hierarchical /D^S inclusive of network-based and host-based intrusion detection system with due consideration to their characteristics on ad hoc on4emand distance vector routing protocol (AODV+).